Reconstruction of the Election System Following Constitutional Court Decision Number 135/PUU-XXII/2024: A Legal-Normative Review of the Separation of National and Regional Elections - Isnaeni, MH. (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The Constitutional Court Decision Number 135/PUU-XXII/2024 marks a significant milestone in the reconstruction of Indonesia’s electoral system, particularly concerning the separation between national elections—including the presidential, DPR, and DPD elections—and regional elections for governors, regents/mayors, and local legislative councils (DPRD). This article focuses on analyzing the normative and institutional implications of the decision and its impact on the legal architecture of elections in Indonesia. Employing a normative juridical approach and drawing comparative insights from electoral systems in other democratic countries, this study finds that the separation of elections has the potential to enhance substantive democratic quality, improve voter focus, and reduce the technical and administrative burden on electoral bodies. Nonetheless, such a policy demands a comprehensive restructuring of the legal framework, including institutional design, the sequencing of electoral stages, and regulatory harmonization between central and regional authorities. Thus, the findings of this research serve as a conceptual foundation for advancing an electoral system that is more effective, representative, and aligned with democratic integrity principles.